2020
DOI: 10.1002/ijc.32862
|View full text |Cite
|
Sign up to set email alerts
|

Modulating sphingosine‐1‐phosphate receptors to improve chemotherapy efficacy against Ewing sarcoma

Abstract: Tumor vasculature is innately dysfunctional. Poorly functional tumor vessels inefficiently deliver chemotherapy to tumor cells; vessel hyper‐permeability promotes chemotherapy delivery primarily to a tumor's periphery. Here, we identify a method for enhancing chemotherapy efficacy in Ewing sarcoma (ES) in mice by modulating tumor vessel permeability. Vessel permeability is partially controlled by the G protein‐coupled Sphinosine‐1‐phosphate receptors 1 and 2 (S1PR1 and S1PR2) on endothelial cells. S1PR1 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The underlying mechanism might be the different responses of S1PRs to different concentrations of S1P. Lower concentrations of S1P are previously reported to mainly activate S1PR1, while conversely, high concentrations of S1P activated S1PR2 ( Marmonti et al, 2020 ). In our study, S1P1and three maintains stable in any concentration of thrombin stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism might be the different responses of S1PRs to different concentrations of S1P. Lower concentrations of S1P are previously reported to mainly activate S1PR1, while conversely, high concentrations of S1P activated S1PR2 ( Marmonti et al, 2020 ). In our study, S1P1and three maintains stable in any concentration of thrombin stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activated S1PR1 and S1PR3 is associated with a protective barrier effect ( Sanna et al, 2006 ), whereas the activation of S1P receptor 2 (S1PR2) destabilizes this effect ( Sanchez et al, 2007 ). Recently, the balance between S1PR1 and S1PR2 signaling in a specific vascular bed was reported to determine endothelial responses to S1P in vivo ( Lee et al, 2009 ; Chen et al, 2015 ; Marmonti et al, 2020 ) . Crucially, the effect of S1P on vascular permeability strongly depends on its concentration.…”
Section: Introductionmentioning
confidence: 99%
“…FTY720 can cause lymphopenia [ 77 , 78 , 79 ], which impairs immune response against bacterial or viral infection. Treatment with JTE013 exhibited both beneficial effects and side effects associated with tumor growth, chemotherapy, and metastasis [ 80 , 81 , 82 , 83 , 84 ]. Treatment with JTE013 enhanced tumor cell migration, which can potentially lead to tumor invasion and metastasis [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies demonstrated that treatment with JTE013 was able to inhibit the proliferation of tumor cells in vitro [ 82 ] and in vivo [ 81 ]. Treatment with JTE013 also improved chemotherapy efficacy against Ewing sarcoma [ 83 ] and sensitized 5-fluorouracil chemotherapy against colorectal cancer [ 84 ]. Second, JTE013 might be unstable in vivo and is rapidly metabolized in the liver [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a potential involvement of tumour, rather than vessel, S1P 1 and/or S1P 2 was not excluded. Despite this, there may be potential for adjuvant S1P 1 agonists and/or S1P 2 antagonists with standard chemotherapy for Ewing sarcoma patients [37]. In contrast, the S1P 1 functional antagonist, Siponimod, reduces angiogenesis and tumour growth in a mouse model of diffuse large B‐cell lymphoma (DLBCL).…”
Section: Role Of S1p In Tumour Neovascularisation and Metastasismentioning
confidence: 99%